Farmers Perceptions of Sustainable Lowland Rice Farming Through Economic, Social, and Environmental Dimensions in Motilango Village, Tilongkabila District - Jasmani S Jama; Asda Rauf; Amelia Murtisari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze farmers’ perceptions of sustainable lowland rice farming through the economic, social, and environmental dimensions, as well as to examine the relationship between farmers’ characteristics and their perceptions of sustainable farming. Methods: This is an empirical research article using a descriptive quantitative approach. The research was conducted in Motilango Village, Tilongkabila District, Bone Bolango Regency, Gorontalo Province. Data were collected through interviews with 40 respondents selected purposively based on the criterion of having at least 15 years of farming experience. Data analysis employed descriptive statistics, Likert scale scoring, and the Chi-Square (χ²) test. Results: The findings reveal that farmers’ perceptions of sustainable agriculture were categorized as fairly important for the economic (78.1%) and social (77.6%) dimensions, and important for the environmental dimension (89.5%), with an overall average of 81.73%. The factor significantly associated with farmers’ perceptions was the availability of agricultural information from sources other than extension services, particularly in the environmental dimension (p < 0.05). Novelty: This highlights that more diverse access to information, especially through social media and farmer groups, serves as a crucial determinant in shaping farmers’ perceptions of sustainability. Originality: Theoretically, this study enriches the literature on farmers’ perceptions by emphasizing the critical role of non-extension information sources in fostering sustainability awareness. Practically, the findings provide a foundation for designing policies, extension programs, and strengthening farmer groups to promote the adoption of locally based sustainable rice farming systems. Conclusion: This study contributes by offering a comprehensive understanding of farmers’ perceptions and the influencing factors, and by serving as a basis for strategies to strengthen local-based sustainable farming systems. Type of Paper: Empirical research article.